Study of polonisms in Belarusian linguistics and attitude toward them (ХІХ century – 1930s) - Svistunova, Maryna I. (Journal of the Belarusian State University. Philology, 2019)
The polonisms are considered in the article as an object of study in Belarusian linguistics from the XIX century to the first 30 years of the XX century. Main academic sources for the XIX century are the works of K. Kalajdovich, J. Chachot, F. Golotuzov, I. Nosovich, J. Karski. Evaluation of the using of polonisms during this period by M. H. Bulahau and L. M. Shakun are given in this article. The articles of M. Bajkou, I. Vouk-Levanovich, V. Lastouski, J. Liosik, S. Nekrashevich, L. Cviatkou are the background for studying the attitude towards polonisms in 1920 –30s. It’s determined that unknown today article «Polish Element in Belarusian Language» by L. Cviatkou was the only special article for this time and stayed in the state of manuscript. The works of A. J. Bahankou, M. H. Bulahau, I. K. Hermanovich, L. M. Shakun are taken as an example of the attitude toward polonisms and considered.